A Systematic Review of the Use of Physiological Tests Assessing the Acute Response to Treatment During Exacerbations of COPD (with a Focus on Small Airway Function). (1st November 2020) - Alobaidi, Nowaf Y; Almeshari, Mohammed; Stockley, James A.; Sapey, Elizabeth; Edgar, Ross G.
Abstract: Exacerbations are prevalent in Chronic Obstructive Pulmonary Disease (COPD) patients and associated with poor clinical outcomes. Currently, there is a lack of sensitive and specific tools that can objectively identify exacerbations and assess their progress or treatment response. FEV1 is often reported as a study outcome, but it has significant limitations. Studies have suggested that small airways measures might provide physiological biomarkers during exacerbations. Therefore, this study was done to assess which physiological tests of small airways function have been used in the acute setting during exacerbations of COPD and the evidence to support their use. An electronic databases search was conducted in April 2019. A standard systematic review methodology was used. Eligible studies were those of ≥10 participants that compared at least one small airway test with FEV1 to assess response to treatment with baseline and a follow-up measurement ≤2 months after. Analyses were narrative. Of 1436 screened studies, seven studies were eligible. There was heterogeneity in which tests of small airways were used and three different small airways measures were reported. Studies were small (including 20 to 87 subjects). Six articles reported improvements in small airway measurements during the recovery from exacerbation which correlated with FEV1 . Included studies varied in their timing and duration of the assessment. There is some evidence to support the use of small airway tests in acute exacerbations of COPD. However, studies have been small with different tests being utilized. Further studies to determine the usefulness of each test may be of interest.